A modified aluminum powder and its preparation process and application in preparing anode foil of aluminum electrolytic capacitor
By first humidifying and then drying the aluminum powder, the hole structure is formed, and the conductivity and bonding ability are improved, the problem of insufficient thermal conductivity of the anode foil of the aluminum electrolytic capacitor is solved, and the specific capacitance is significantly improved and the environmentally friendly production process is achieved.
Patent Information
- Application Number
- CN202411906315.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
AI Technical Summary
The thermal conductivity of the anode foil of the existing aluminum electrolytic capacitor is not excellent enough, has a small viscosity and a small surface area, and the acidic waste liquid generated during the production of corrosive foil is seriously polluted to the environment.
The aluminum powder is modified by humidification and then drying, forming a large number of hole structures, improving the conductivity and binding ability with solvents, thereby providing high-performance support in the preparation of the anode foil of the aluminum electrolytic capacitor.
The conductivity and bonding ability of the modified aluminum powder are significantly improved. The modified aluminum powder can be dispersed more evenly in the preparation of the anode foil of the aluminum electrolytic capacitor, providing high-performance support, and the specific capacity of the anode foil has also been significantly improved.
Smart Images

Figure CN119747647A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum electrolytic capacitors, and in particular relates to a modified aluminum powder and a preparation process thereof and an application of the modified aluminum powder in preparing an anode foil of an aluminum electrolytic capacitor. Background Art
[0002] Aluminum electrolytic capacitors are one of the indispensable components in modern electronic products. They have the characteristics of excellent electrical properties, large capacity, low cost, easy processing, and easy use. They are currently widely used in household appliances, power supplies, hybrid power devices, aerospace, and military fields.
[0003] At present, most of the anode foils of aluminum electrolytic capacitors are made of traditional etching foils. However, the research on etching foils has reached its theoretical limit. The growth of the specific capacity of industrially formed foils has almost stagnated, and the acidic waste liquid generated during the production of etching foils seriously pollutes the environment.
[0004] In recent years, the technology of using aluminum powder slurry to coat and sinter to prepare aluminum electrolytic capacitor anode foil has begun to emerge. For example, Chinese invention patent with announcement number CN114523112B discloses a preparation process for porous electrode foil, which includes the following steps: (1) mixing aluminum powder, valve metal oxide powder, binder and solvent according to a preset mass percentage to obtain a mixed fluid; (2) coating the mixed fluid on at least one side of an aluminum foil substrate, drying and compacting to obtain a composite aluminum foil; (3) subjecting the composite aluminum foil to a staged sintering treatment, and anodizing the sintered foil to obtain a porous electrode foil.
[0005] However, the aluminum powder products currently used in the thermal and electrical conductivity industries generally have problems such as insufficient thermal and electrical conductivity, low viscosity, and small specific surface area. Summary of the invention
[0006] The invention aims to provide a modified aluminum powder and a preparation process thereof and application in the preparation of an aluminum electrolytic capacitor anode foil, wherein the preparation process can improve the electrical conductivity, viscosity, and solvent binding ability of the aluminum powder.
[0007] To achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:
[0008] The present invention first provides a preparation process of modified aluminum powder, which comprises the following steps:
[0009] (1) placing the aluminum powder in a constant temperature and humidity environment at a temperature of 45-55°C and a humidity of 80-95% for 40-120 minutes;
[0010] (2) After the humidification treatment is completed, the modified aluminum powder is dried at 60-80° C. for 240-360 min to obtain the modified aluminum powder.
[0011] The present invention adopts the method of first humidifying and then drying to modify the aluminum powder. A large number of pore structures are formed on the surface of the modified aluminum powder, and the surface area is greatly increased, which not only makes the conductivity of the modified aluminum powder significantly improved (3.5×10 7 S / m), and the binding ability of the modified aluminum powder with the solvent is also significantly improved. The modified aluminum powder can be more evenly dispersed in the aluminum powder slurry in subsequent applications, providing high-performance support for the stirring of the aluminum powder slurry, foil surface sintering and other steps.
[0012] Preferably, in step (1) of the above preparation process, aluminum powder with a purity greater than 99.98% and an initial humidity less than 0.06% is selected. High-purity aluminum powder has a lower impurity content, which helps to improve the stability and safety of aluminum powder during the modification process and avoid impurities from introducing unnecessary chemical reactions or reducing the overall performance of the material; and low-humidity aluminum powder is selected to avoid agglomeration before modification, thereby affecting the modification efficiency.
[0013] Preferably, in step (1) of the above preparation process, the aluminum powder is passed through a 200-mesh sieve and then spread out to a thickness of 10-100 mm; and then sent into a constant temperature and humidity chamber.
[0014] Preferably, in step (1) of the above preparation process, the humidification treatment is performed for 40-120 minutes at a temperature of 48-52° C. and a humidity of 85-90%. A temperature of 48-52° C. is conducive to the modification reaction of aluminum powder particles, and a humidity of 85-90% allows the aluminum powder to be fully in contact with water; a humidification time that is too short will result in insufficient modification of the aluminum powder, and a humidification time that is too long will result in complete oxidation of the aluminum powder, so the present invention sets the humidification time to 40-120 minutes.
[0015] Preferably, in step (2) of the above preparation process, the aluminum powder is dried at 70° C. for 240-360 min to effectively remove moisture from the aluminum powder.
[0016] The present invention also provides a modified aluminum powder, which is prepared by adopting the above-mentioned preparation process.
[0017] The present invention also provides the use of the modified aluminum powder in preparing an anode foil of an aluminum electrolytic capacitor, the use comprising:
[0018] (a) mixing the modified aluminum powder, valve metal oxide powder, binder and solvent according to a preset mass percentage to obtain an aluminum powder slurry;
[0019] (b) coating the aluminum powder slurry on at least one side of an aluminum foil substrate, drying and compacting to obtain a composite foil;
[0020] (c) sequentially subjecting the composite foil to sintering and chemical treatment to obtain the aluminum electrolytic capacitor anode foil.
[0021] Preferably, in step (a), the valve metal oxide is at least one of titanium dioxide, tantalum pentoxide or niobium pentoxide;
[0022] The binder is at least one of polyvinylidene fluoride, methyl cellulose, ethyl cellulose, trityl cellulose, cyanoethyl cellulose, carboxymethyl cellulose, carboxyethyl cellulose, aminoethyl cellulose or ethoxy cellulose;
[0023] The solvent is water or an organic solvent;
[0024] The mass percentages of the raw materials in the mixed fluid are: 50wt.% to 60wt.% modified aluminum powder, 0.02wt.% to 2.5wt.% valve metal oxide powder, 3wt.% to 10wt.% binder, and 30wt.% to 45wt.% solvent.
[0025] The present invention also provides an anode foil for an aluminum electrolytic capacitor, which comprises an aluminum foil substrate and a composite film formed on at least one side of the aluminum foil substrate, wherein the raw material of the composite film contains the modified aluminum powder mentioned above.
[0026] The specific operation method is: use the slurry prepared by the modified aluminum powder to coat both sides of a 30μm aluminum foil substrate, control the coating thickness to 50μm, and obtain a composite foil with an overall thickness of 130μm. By sintering and chemically forming the composite foil, an aluminum electrolytic capacitor anode foil is finally obtained.
[0027] The specific capacitance of the anode foil made of the modified aluminum powder is significantly improved, among which the specific capacitance of the 520V anode foil is greater than 1.00μF / cm 2 .
[0028] Compared with the prior art, the technical effects of the present invention are embodied in:
[0029] (1) The present invention adopts the method of first humidifying and then drying to modify the aluminum powder. A large number of pore structures are formed on the surface of the modified aluminum powder, and the surface area is greatly increased, which not only significantly improves the conductivity of the modified aluminum powder (3.5×10 7 S / m), and the binding ability of the modified aluminum powder with the solvent is also significantly improved. The modified aluminum powder can be more evenly dispersed in the aluminum powder slurry in subsequent applications, providing high-performance support for the stirring of the aluminum powder slurry, foil surface sintering and other steps.
[0030] (2) The specific capacitance of the anode foil prepared by the modified aluminum powder of the present invention is significantly improved, wherein the specific capacitance of the 520V anode foil is greater than 1.00 μF / cm 2. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is the microscopic morphology of unmodified aluminum powder;
[0032] Figure 2 This is a microscopic morphology diagram of the modified aluminum powder of the present invention. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0034] Example 1
[0035] The present embodiment provides a modified aluminum powder, and its preparation process comprises the following steps:
[0036] (1) The aluminum powder was placed in a constant temperature and humidity environment at 50°C and 85% humidity for 40 minutes;
[0037] Specifically, 300 g of aluminum powder with a purity greater than 99.98% and an initial humidity less than 0.06% was first selected, and the aluminum powder was spread on a dust-free carrier through a 200-mesh screen with a thickness of 100 mm; then the powder was placed in a constant temperature and humidity chamber for 40 minutes of humidification treatment, with the humidification humidity controlled at 85% and the temperature at 50°C;
[0038] (2) After the humidification treatment, the modified aluminum powder of this embodiment is obtained by drying at 70° C. for 240 min;
[0039] Specifically, after the humidification time is over, the humidification function of the constant temperature and humidity chamber is turned off, the temperature is adjusted to 70° C. and dried for 240 minutes; after the drying is completed, it is naturally cooled to room temperature to obtain the modified aluminum powder of this embodiment.
[0040] Example 2
[0041] The present embodiment provides a modified aluminum powder, and its preparation process comprises the following steps:
[0042] (1) The aluminum powder was placed in a constant temperature and humidity environment at 50°C and 85% humidity for 80 minutes;
[0043] Specifically, 300 g of aluminum powder with a purity greater than 99.98% and an initial humidity less than 0.06% was first selected, and the aluminum powder was spread on a dust-free carrier through a 200-mesh screen with a thickness of 100 mm; then the powder was placed in a constant temperature and humidity chamber for 80 minutes of humidification treatment, with the humidification humidity controlled at 85% and the temperature at 50°C;
[0044] (2) After the humidification treatment, the modified aluminum powder of this embodiment is obtained by drying at 70° C. for 240 min;
[0045] Specifically, after the humidification time is over, the humidification function of the constant temperature and humidity chamber is turned off, the temperature is adjusted to 70° C. and dried for 240 minutes; after the drying is completed, it is naturally cooled to room temperature to obtain the modified aluminum powder of this embodiment.
[0046] Example 3
[0047] The present embodiment provides a modified aluminum powder, and its preparation process comprises the following steps:
[0048] (1) The aluminum powder was placed in a constant temperature and humidity environment at 50°C and 90% humidity for 120 minutes;
[0049] Specifically, 300 g of aluminum powder with a purity greater than 99.98% and an initial humidity less than 0.06% was first selected, and the aluminum powder was spread on a dust-free carrier through a 200-mesh screen with a thickness of 100 mm; then the powder was placed in a constant temperature and humidity chamber for humidification treatment for 120 minutes, with the humidity controlled at 90% and the temperature at 50°C;
[0050] (2) After the humidification treatment, the modified aluminum powder of this embodiment is obtained by drying at 70° C. for 240 min;
[0051] Specifically, after the humidification time is over, the humidification function of the constant temperature and humidity chamber is turned off, the temperature is adjusted to 70° C. and dried for 240 minutes; after the drying is completed, it is naturally cooled to room temperature to obtain the modified aluminum powder of this embodiment.
[0052] Example 4
[0053] The present embodiment is a modified aluminum powder, and its preparation process is the same as that of the embodiment 3, except that:
[0054] In step (1), the temperature of the humidification treatment is 45°C.
[0055] Example 5
[0056] The present embodiment is a modified aluminum powder, and its preparation process is the same as that of the embodiment 3, except that:
[0057] In step (1), the temperature of the humidification treatment is 55°C.
[0058] Example 6
[0059] The present embodiment is a modified aluminum powder, and its preparation process is the same as that of the embodiment 3, except that:
[0060] In step (1), the humidity of the humidification treatment is 80%.
[0061] Example 7
[0062] The present embodiment is a modified aluminum powder, and its preparation process is the same as that of the embodiment 3, except that:
[0063] In step (1), the humidity of the humidification treatment is 95%.
[0064] Example 8
[0065] The present embodiment is a modified aluminum powder, and its preparation process is the same as that of the embodiment 3, except that:
[0066] In step (2), the drying temperature is 65°C.
[0067] Example 9
[0068] The present embodiment is a modified aluminum powder, and its preparation process is the same as that of the embodiment 3, except that:
[0069] In step (2), the drying temperature is 80°C.
[0070] Microscopic observation of the modified aluminum powders obtained in Examples 1-9 revealed that many tiny pore structures appeared in the modified aluminum powders of the present invention, which greatly increased the surface area of the modified aluminum powders ( Figure 2 The microstructure of the modified aluminum powder obtained in Example 1 is shown in FIG. 1 ); relatively speaking, the surface roughness of the aluminum powder before modification is relatively poor (eg Figure 1 shown).
[0071] The conductivity, viscosity, and solvent binding ability of the modified aluminum powders obtained in Examples 1-9 were tested. The test results are shown in Table 1.
[0072] Table 1 Performance analysis of aluminum powder before and after modification
[0073] Conductivity Viscosity increase rate Solvent binding ability Aluminum powder before modification <![CDATA[3.08×10 7 S / m]]> / Normal; a small amount of aluminum powder sinks to the bottom Example 1 <![CDATA[3.73×10 7 S / m]]> 27% Excellent; aluminum powder is evenly dispersed Example 2 <![CDATA[3.75×10 7 S / m]]> 26% Excellent; aluminum powder is evenly dispersed Example 3 <![CDATA[3.81×10 7 S / m]]> 31% Excellent; aluminum powder is evenly dispersed Example 4 <![CDATA[3.59×10 7 S / m]]> 24% Excellent; aluminum powder is evenly dispersed Example 5 <![CDATA[3.78×10 7 S / m]]> 27% Excellent; aluminum powder is evenly dispersed Example 6 <![CDATA[3.56×10 7 S / m]]> 23% Excellent; aluminum powder is evenly dispersed Example 7 <![CDATA[3.77×10 7 S / m]]> 30% Excellent; aluminum powder is evenly dispersed Example 8 <![CDATA[3.79×10 7 S / m]]> 31% Excellent; aluminum powder is evenly dispersed Example 9 <![CDATA[3.80×10 7 S / m]]> 29% Excellent; aluminum powder is evenly dispersed
[0074] It can be seen from Table 1 that, compared with the aluminum powder before modification, the conductivity, viscosity and solvent binding ability of each modified aluminum powder of the present invention are significantly improved.
[0075] Examples 10-18
[0076] The present embodiment is an aluminum electrolytic capacitor anode foil, which is made of the modified aluminum powders prepared in the embodiments 1-9, and the preparation process is the same as that described in the embodiment 2 of the Chinese invention patent with the announcement number CN114523112B, and will not be described in detail in the present embodiment. Obviously, other methods can also be used.
[0077] Comparative Example 1
[0078] This comparative example is an aluminum electrolytic capacitor anode foil, which is made of unmodified aluminum powder, and the preparation process is the same as that of Example 10.
[0079] The thickness and specific volume of the anode foils prepared in Examples 10-18 and Comparative Example 1 were tested. The test results are shown in Table 2.
[0080] Table 2 Specific capacitance test results of 520V anode foil
[0081] 520V anode foil thickness specific volume Example 10 131.0μm <![CDATA[1.13μF / cm 2 ]]> Embodiment 11 131.5μm <![CDATA[1.08μF / cm 2 ]]> Example 12 131.0μm <![CDATA[1.14μF / cm 2 ]]> Embodiment 13 130.5μm <![CDATA[1.05μF / cm 2 ]]> Embodiment 14 131.0μm <![CDATA[1.12μF / cm 2 ]]> Embodiment 15 131.0μm <![CDATA[1.07μF / cm 2 ]]> Example 16 131.5μm <![CDATA[1.16μF / cm 2 ]]> Embodiment 17 131.5μm <![CDATA[1.09μF / cm 2 ]]> Embodiment 18 130.5μm <![CDATA[1.12μF / cm 2 ]]> Comparative Example 1 131.5μm <![CDATA[0.81μF / cm 2 ]]>
[0082] As shown in Table 2, compared with Comparative Example 1, the specific capacitance of the anode foils prepared in Examples 10-18 is significantly improved, all reaching 1.00 μF / cm 2 above.
Claims
1. A process for preparing modified aluminum powder, characterized in that: The following steps are involved: (1) placing the aluminum powder in a constant temperature and humidity environment at a temperature of 45-55°C and a humidity of 80-95% for 40-120 minutes; (2) After the humidification treatment is completed, the modified aluminum powder is dried at 60-80° C. for 240-360 min to obtain the modified aluminum powder.
2. The preparation process according to claim 1, characterized in that: In step (1), aluminum powder with a purity greater than 99.98% and an initial humidity less than 0.06% is selected.
3. The preparation process according to claim 1, characterized in that: In step (1), the aluminum powder is passed through a 200-mesh sieve and then spread out to a thickness of 10-100 mm; and then placed in a constant temperature and humidity chamber.
4. The preparation process according to claim 1, characterized in that: In step (1), the humidification treatment is performed for 40-120 minutes at a temperature of 48-52° C. and a humidity of 85-90%.
5. The preparation process according to claim 1, characterized in that: In step (2), drying is performed at 70° C. for 240 min.
6. A modified aluminum powder, characterized in that: The method is prepared by the preparation process as described in any one of claims 1 to 5.
7. Use of the modified aluminum powder as claimed in claim 6 in preparing anode foil of aluminum electrolytic capacitors.
8. The use according to claim 7, characterized in that include: (a) mixing the modified aluminum powder, valve metal oxide powder, binder and solvent according to a preset mass percentage to obtain an aluminum powder slurry; (b) coating the aluminum powder slurry on at least one side of an aluminum foil substrate, drying and compacting to obtain a composite foil; (c) sequentially subjecting the composite foil to sintering and chemical treatment to obtain the aluminum electrolytic capacitor anode foil.
9. The use according to claim 8, characterized in that In step (a), the valve metal oxide is at least one of titanium dioxide, tantalum pentoxide or niobium pentoxide; The binder is at least one of polyvinylidene fluoride, methyl cellulose, ethyl cellulose, trityl cellulose, cyanoethyl cellulose, carboxymethyl cellulose, carboxyethyl cellulose, aminoethyl cellulose or ethoxy cellulose; The solvent is water or an organic solvent; The mass percentages of the raw materials in the mixed fluid are: 50wt.% to 60wt.% modified aluminum powder, 0.02wt.% to 2.5wt.% valve metal oxide powder, 3wt.% to 10wt.% binder, and 30wt.% to 45wt.% solvent.
10. An aluminum electrolytic capacitor anode foil, characterized in that: It comprises an aluminum foil substrate and a composite film formed on at least one side of the aluminum foil substrate, wherein the raw material of the composite film contains the modified aluminum powder as described in claim 6.
Citation Information
Patent Citations
A porous electrode foil and its preparation process
CN114523112B